2009
DOI: 10.1016/j.fgb.2009.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduced genomic potential for secreted plant cell-wall-degrading enzymes in the ectomycorrhizal fungus Amanita bisporigera, based on the secretome of Trichoderma reesei

Abstract: Based on the analysis of its genome sequence, the ectomycorrhizal (ECM) basidiomycetous fungus Laccaria bicolor was shown to be lacking many of the major classes of secreted enzymes that depolymerize plant cell wall polysaccharides. To test whether this is also a feature of other ECM fungi, we searched a survey genome database of Amanita bisporigera with the proteins found in the secretome of Trichoderma reesei (syn. Hypocrea jecorina), a biochemically well-characterized industrial fungus. Additional proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 45 publications
(63 reference statements)
3
112
0
1
Order By: Relevance
“…A reduced set of plant cell-wall degrading enzymes (PCWDEs) has also been reported for Amanita bisporigena by Nagendran et al (2009), who showed that this ectomycorrhizal fungus lacks the genomic potential to biosynthesize many extracellular enzymes that are active on the linkages in the plant cell wall and, in particular, exhibits a loss of several key cellulase genes. A large-scale comparative genomics analysis of fungal genomes with different life-styles, including a dozen ectomycorrhizal fungi, has confirmed that the latter have a reduced complement of genes encoding PCWDEs, thus suggesting that, during their evolution, ectomycorrhizal fungi have lost much of the enzymatic apparatus of their ancestral wood decayers .…”
Section: Introductionmentioning
confidence: 83%
“…A reduced set of plant cell-wall degrading enzymes (PCWDEs) has also been reported for Amanita bisporigena by Nagendran et al (2009), who showed that this ectomycorrhizal fungus lacks the genomic potential to biosynthesize many extracellular enzymes that are active on the linkages in the plant cell wall and, in particular, exhibits a loss of several key cellulase genes. A large-scale comparative genomics analysis of fungal genomes with different life-styles, including a dozen ectomycorrhizal fungi, has confirmed that the latter have a reduced complement of genes encoding PCWDEs, thus suggesting that, during their evolution, ectomycorrhizal fungi have lost much of the enzymatic apparatus of their ancestral wood decayers .…”
Section: Introductionmentioning
confidence: 83%
“…We demonstrated for the first time that the exoproteome of Fusarium graminearum grown in presence of plant material was rich in various CWDE: more than 80 different proteins, half of them being putatively involved in cell wall digestion were recovered from culture supernatant (Phalip et al, 2005). It is noticeable that later, rather the same number of proteins was found to be secreted by Trichoderma reesei grown on corn cell wall (Nagendran et al, 2009). Commercial preparation Spezyme® used for biomass hydrolysis contains also more than 80 different proteins.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 88%
“…6. Nature of putative secreted CWDE found in Trichoderma reesei grown on corn cops (left; Nagendran et al, 2009) and in Fusarium graminearum grown on hop (right; Phalip et al, 2005).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Currently available commercial enzyme cocktails are complex and poorly defined mixtures of many proteins (Nagendran et al, 2009), and they are adapted mainly for use on acid-pretreated corn stover. In order to accelerate the development of better enzyme cocktails, several laboratories have developed high-throughput platforms for enzyme discovery and characterization.…”
Section: Discussionmentioning
confidence: 99%